Analysis of Human Resource Management in Government Bureaucracy in Indonesia - Budi Rismayadi (Journal Arbitrase : Economy, Management and Accounting, 2024)
This research aims to analyze human resource management (HR) in the context of government bureaucracy in Indonesia. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of bureaucratic reform in Indonesia has achieved progress in improving the performance of state apparatus and transforming public services. However, there are significant challenges related to uncertainty in publishing public service information and limited use of information technology. Bureaucratic transformation, especially in human resource management and the application of HR values, has formed a strong foundation for creating a more responsive and efficient work environment. To optimize the potential for this transformation, it is necessary to increase human resource capacity related to information technology and develop an organizational culture that supports innovation. In conclusion, Indonesia is on a positive path towards a bureaucracy that is more adaptive, innovative and oriented towards quality public services, provided that it needs to overcome the challenges that still exist.